Optimal dosage and duration of pivmecillinam treatment for uncomplicated lower urinary tract infections: a systematic review and meta-analysis - Pinart, Mariona; Jensen, Katrin; Proctor, Tanja (International journal of infectious diseases, 2017)
Summary Objective To compare the efficacy and safety of different pivmecillinam (PIV) regimes for uncomplicated lower urinary tract infections (UTIs). Methods The MEDLINE, Embase, and Cochrane Library databases were searched. Randomized controlled clinical trials (RCTs) involving adults or children with symptoms suggestive of uncomplicated UTI and that compared different PIV regimes or PIV versus other antibiotics were included. Meta-analyses were conducted to obtain direct and indirect efficacy estimates. PIV regimes were categorized into high total dosage, moderate total dosage, and low total dosage. The risk of bias was evaluated using the Cochrane tool. Results Twenty-four RCTs were identified. No difference in clinical cure was found for the high vs. moderate (short-term: risk ratio (RR) 1.01, p=0.813; long term: RR 1.09, p=0.174) or high vs. low dosage comparisons (mean difference 0, 95% confidence interval −0.44 to 0.45, p=1). For bacteriological cure, comparisons of high vs. moderate dosage (short term: RR 1.05, p=0.056; long term: RR 1.05, p=0.131) and high vs. low dosage (short term: RR 1.02, p=0.759; long term: RR 1.13, p=0.247) showed a trend in favor of the high dosage treatment. Results for relapse, re-infection, and failure were inconclusive and not statistically significant. Patients treated with high dosages were 40% (p=0.062) and 44% (p=0.293) more likely to report mild to moderate adverse events. Conclusions There is insufficient evidence to support the use of an optimal combination of dosage, frequency, and duration of PIV therapy for the treatment of uncomplicated lower UTI. Evidence is limited due to the high risk of bias, poor reporting, and heterogeneous study data.